Rebecca to the rescue - Greene, Jacqueline Dembar (American girls collection, 2009)
While celebrating her brother's Bar Mitzvah on Coney Island, nine-year-old Rebecca Rubin disobeys by going off on her own, leaving her cousin Ana, a recent immigrant, alone.